Pengembangan Pembelajaran Area Dan Sentra Berbasis Alat Permainan Edukatif Di TK Pertiwi Gondangrejo Karanganyar Tahun 2016/2017 - Chasanah, Uswatun, Prof. Dr. Sutama, M.Pd, Dr. Suyatmini, M.Si (2017)
The purpose of this study is to describe: (1) Learning Areas and centers held in TK Pertiwi Gondangrejo Karanganyar; (2) Learning Development Areas And centers using Games Educational Tool in TK Pertiwi Gondangrejo Karanganyar; (3) Test the Effectiveness of Learning Development Areas And centers with Games Educational Tool In TK Pertiwi Gondangrejo Karanganyar. This research included in research and development. "Research and Development (Research and Development) is a process or steps to develop a new product or improve existing products, which can beacounted for.More Research and development is a method of connecting or breaker gap anatar basic research with applied research. The design of this study using a model system consisting of planning (planning), action (acting), observation (observing) and reflection (reflecting) This research data obtained through a class action (action research) with learning to do know before and after action.The data obtained were analyzed by flow through phase model of data reduction, data presentation and verification stages of conclusion.The results of this study can be concluded that the development of learning Areas and Centers of educational games based tool to improve learning outcomes of kindergarten children Pertiwi Gondangrejo Karanganyar. This is evident from the realization of the learning areas and centers action first cycle the average value of 8.3, the second cycle of 8.8, 9.4 Cycle III always changes increase learning outcomes of children